2016
DOI: 10.1136/bmjopen-2015-010004
|View full text |Cite
|
Sign up to set email alerts
|

Association between neighbourhood air pollution concentrations and dispensed medication for psychiatric disorders in a large longitudinal cohort of Swedish children and adolescents

Abstract: ObjectiveTo investigate associations between exposure to air pollution and child and adolescent mental health.DesignObservational study.SettingSwedish National Register data on dispensed medications for a broad range of psychiatric disorders, including sedative medications, sleeping pills and antipsychotic medications, together with socioeconomic and demographic data and a national land use regression model for air pollution concentrations for NO2, PM10 and PM2.5.ParticipantsThe entire population under 18 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 58 publications
5
65
3
2
Order By: Relevance
“…Contrary to our hypothesis, we did not find a positive association between most of the air pollutants considered in our study, such as PM 10 , PM 2.5 , CO and NO 2 . This is in contrast with previous literature on this subject (Szyszkowicz et al, 2009(Szyszkowicz et al, , 2010(Szyszkowicz et al, , 2018Mehta et al, 2015;Power et al, 2015;Chen et al, 2018;Duan et al, 2018;Eguchi et al, 2018;Kim et al, 2018;Oudin et al, 2018;Shin et al, 2018;Song et al, 2018;Bai et al, 2019;Lee et al, 2019;Qiu et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our hypothesis, we did not find a positive association between most of the air pollutants considered in our study, such as PM 10 , PM 2.5 , CO and NO 2 . This is in contrast with previous literature on this subject (Szyszkowicz et al, 2009(Szyszkowicz et al, , 2010(Szyszkowicz et al, , 2018Mehta et al, 2015;Power et al, 2015;Chen et al, 2018;Duan et al, 2018;Eguchi et al, 2018;Kim et al, 2018;Oudin et al, 2018;Shin et al, 2018;Song et al, 2018;Bai et al, 2019;Lee et al, 2019;Qiu et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, it has been recently hypothesised that exposure to xenobiotic heavy metals such as lead and cadmiumconstituents of air pollution such as particulate matter and nitrogen and sulphur oxides, organic solvents and other environmental pollutantscould be component causes for schizophrenia and other psychotic disorders . Moreover, recent studies in Sweden found that ambient air particle concentrations are associated with the number of visits to psychiatric emergency units in the warm season, suggesting that air pollution may exacerbate an underlying psychiatric disorder, or increase mental distress, even in areas with comparatively low levels of air pollution (Oudin et al, 2018). Similarly, long-term exposure to ambient air pollution could be an independent risk factor for mental health disorders ranging from subjective stress to depressive disorders and suicidal ideation .…”
Section: Introductionmentioning
confidence: 99%
“…또한 개인에게 동일한 조건의 대기오염 노출 시, 개인의 쾌락적 행복을 떨어뜨리고, 우울증 증상 비율을 증가시켰다 (Zhang et al, 2017). 특히, 대기오염의 농도가 높은 지역에 사는 아동⋅청소년일수록 사후관리 중 정신질환 관련 약물치 료를 받을 가능성이 커짐이 보고되었다 (Oudin et al, 2016). 영국 코호트 조사결과, 12살의 아동이 높은 미세먼지 농도에 노출될수록 18살이 되었을 때 우울증에 걸릴 확률이 높아졌 다고 한다 (Roberts et al, 2019).…”
unclassified
“…It can also contribute to the formation of particulate matter (PM) and secondary organic particles through photochemical reactions. Increased NOx concentrations not only severely affect human physical health through reduced lung function and psychological health, but also affect aquatic ecosystems through acid deposition and eutrophication of soil and water (Sjöberg et al 2004;Klingberg et al 2009;Bellandar et al 2012;Gustafsson et al 2014;Nilsson Sommar et al 2014;Oudin et al 2016;Taj et al 2016). According to the fifth IPCC assessment report, the total global NOx emissions have increased four-fold from pre-industrial periods to values ranging from 42-47 TgN/yr in 2000 and is projected to increase up to 131 TgN/yr by 2100 (Lamarque et al, 2005).…”
Section: Introductionmentioning
confidence: 99%